„Co mam czynić, aby osiągnąć zbawienie?” Znaczenie ‘ergon’ w Nowym Testamencie - Nawracała, Tomasz (Prymasowskie Wydawnictwo Gaudentinum, 2013)
The author of the article, “What Shall I Do to Be Saved? The Significance of Ergon in the New Testament” stresses that that all the tasks undertakenduring a person,s life define and express his / her essential character. A person’s actions refer not only to his / her past but to the future as well. Each activity acquires a fully human dimension only if it is based on love. Whenever love is missing, evil appers. The author of the Book of Revelation, following the Old Testament tradition, mentions the reward for the good deeds performed by the saints. This article is an attempt at providing an answer to the question about which deeds can be rewarded by God.
What Shall I Do to Be Saved? The Significance of Ergon in the New Testament
Keywords: czyn; odpłata; życie wieczne; ergon; Nowy Testament